2015
DOI: 10.1080/17290376.2015.1086275
|View full text |Cite
|
Sign up to set email alerts
|

Trends in HIV risk behaviour of incoming first-year students at a South African university: 2007–2012

Abstract: The aim of the research on which this article is based was to understand the behavioural changes of the target student population over time to ensure that future prevention programmes are more effective in changing behaviour. This study reports on quantitative data collected at the University of the Western Cape over a six-year period between 2007 and 2012. All the students attending the orientation sessions and who were willing to complete the anonymous questionnaire during each of the six years were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Other studies reported that university students are likely to engage in unprotected sex, have multiple sex partners, engage in sex with older partners, engage in casual sex, and have sex under the influence of alcohol or drugs [ 6 , 7 , 12 , 13 , 14 ]. In South Africa, 61% of students in the institutions of higher education are in a sexual relationship and 15% of them have sex partners who are older than themselves by five or more years [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that university students are likely to engage in unprotected sex, have multiple sex partners, engage in sex with older partners, engage in casual sex, and have sex under the influence of alcohol or drugs [ 6 , 7 , 12 , 13 , 14 ]. In South Africa, 61% of students in the institutions of higher education are in a sexual relationship and 15% of them have sex partners who are older than themselves by five or more years [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the sexual behaviour of adolescents and young adults tend to characterise condomless sex and multiple sexual relationships as risky sexual behaviour [26]. While this is true to some extent, these studies may have overestimated the prevalence of risky sexual behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the literature on adolescents and youth sexual behaviours are dominated by studies examining risky sexual behaviours and its determinants [26]. However, the practice of protective sexual behaviours and its determinants among this cohort has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have explored young people’s sexuality through their parents’ perspective (Madumo, Havenga & Van Aswegen 2015 ; Rau, Radloff, Coetzee, Nardi, Smit & Matebesi 2015 ). Likewise, studies in this field of enquiry among students have generally employed a quantitative approach (Blignaut, Jacobs & Vergnani 2015 ). Furthermore, majority of available literature predominantly focuses on youth risky sexual practices (Simbayi, Shisana, Rehle, Onoya, Jooste, Zungu, et al .…”
Section: Introductionmentioning
confidence: 99%